Cluster externalities, firm capabilities, and the recessionary shock: How the macro-to-micro-transition shapes firm performance during stable times and times of crisis - Christian Hundt; Linus Holtermann; Jonas Steeger; Johannes Bersch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
In this paper, we examine the macro-to-micro-transition of cluster externalities to firms and how it is affected by the macroeconomic instability caused by the recessionary shock of 2008/2009. Using data from 16,166 manufacturing and business services firms nested in 390 German regions, we employ within-firm regression techniques to estimate the impact of crosslevel interactions between firm- and cluster-level determinants on phase-related differences in firm performance between a pre-crisis (2004-2007) and a crisis period (2009-2011). The empirical results validate the existence of a macro-to-micro-transition that evolves best in the case of broad firm-level capabilities and variety-driven externalities. Furthermore, the results indicate that the transition strongly depends on the macroeconomic cycle. While the transition particularly benefits from a stable macroeconomic environment (2004-2007), its mechanisms are interrupted when being exposed to economic turmoil (2009-2011). Yet, the crisisinduced interruption of the transition is mainly restricted to the national recession in 2009. As soon as the macroeconomic pressure diminishes (2010-2011), we observe a reversion of the transmission mechanisms to the pre-crisis level. Our study contributes to the existing literature by corroborating previous findings that the economic performance of firms depends on a working macro-to-micro transition of external resources, which presupposes sufficient cluster externalities and adequate firm-level combinative capabilities. In contrast to previous studies on this topic, the transition mechanism is not modeled as time-invariant. Instead, it is coupled to the prevailing macroeconomic regime.
Keywords: C33; R11; R58; 330; macro-to-micro-transition; combinative capabilities; agglomeration economies; cluster-level externalities; unrelated variety; related variety; macroeconomic regimes; Great Recession; economic resilience